Analysis of the Perception About the Use of a Technological Platform For SME Management - Levin Jeff CHAVEZ; Daniela SALAS-GONZALEZ; Lourdes TAPIA (Communications of International Proceedings, 2022)
In Peru, small and medium-sized enterprises (SMEs) present severe difficulties using and adopting new technologies, in addition to problems of access to business management systems. Through a qualitative analysis process, this research analyzes the perception for the use of a technological platform for the management of SMEs. Sacrificial concepts as a method was used which are early, raw, and potentially flawed concepts made visually or physically and used as a medium for creating reaction, response, and discussion among users and design teams. As the main results of the study, certain characteristics are observed, such as the importance of the level of expertise of the counselor both as a technical level and as soft skills. It is recommended to take into consideration the process of review and evaluation of the quality of the knowledge disseminated.
Keywords: Small and medium-sized enterprises (SMEs); technology adoption; management; Peru